Dr. Ismail Rabbi talks about transforming Africa food system - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Voices of food systems live - the regional discussions on strengthening and transforming local and global food systems_World food day on 16 October 2020.